Socio-economic impacts of privatisation on women made redundant from Sudan's banking and manufacturing sectors - Khalfalla, Limiaa Abdelgafar (2012)
This study focuses on the experiences of a group of women made redundant from public sector institutions in Sudan. It aims to explore the consequences of privatisation and redundancy on women's employment, and economic and social positions.